Rasa Haus pada Pasien Gagal Jantung di Indonesia: Thirst in Heart Failure Patients in Indonesia - Septa Meriana Lumbantoruan; Hsing-Mei Chen (Fakultas Keperawatan Universitas Andalas, 2021)
Thirst is a subjective symptom in patients with heart failure (HF) mostly was studied in the intensity dimension. However, the description of thirst as a complete dimension in patients with HF is needed to be examined. This study aims to describe thirst in hospitalized patients with HF. This was a descriptive cross-sectional study. A total of 85 patients with HF have completed questionnaires including demographics, disease-related factors, and thirst. Thirst was measure in thirst frequency (three items), thirst quality (seven items), thirst intensity (visual analog score 0-100 mm), and thirst distress (thirst distress scale in heart failure). Thirst was reported every day and almost every day (71.7%), lasting for several hours (32.9%) and the thirstiest time was the whole day (47.1%). Thirst quality was described in discomfort (37.6%) and adverse events (31.8). Thirst intensity was in the mid-level and thirst distress have a mean of 24.72. Thirst was burdening on hospitalized patients with HF every day and make them feel distressed.